2016
DOI: 10.5966/sctm.2015-0191
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Conditioned Medium From Human Adipose-Derived Stem Cells Promotes Mouse Liver Regeneration Through JAK/STAT3 Signaling

Abstract: Adipose-derived stem cells (ASCs) mainly exert their function by secreting materials that are collectively termed the secretome. Despite recent attention to the secretome as an alternative to stem cell therapy, the culture conditions for generating optimal secretome contents have not been determined. Therefore, we investigated the role of hypoxic-conditioned media (HCM) from ASCs. Normoxic-conditioned media (NCM) and HCM were obtained after culturing ASCs in 20% O 2 or 1% O 2 for 24 hours, respectively. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 55 publications
2
69
0
Order By: Relevance
“…JAK2 is a major member of the JAK protein family, which can be activated by many cytokines in vivo and phosphorylated with STAT3, an important member of the transcription activator family (STATs) that exists in the nucleus in the form of homologous dimer, to form a JAK2–STAT3 complex; this complex regulates the expression of inflammatory factors, such as TNF‐ α , IL‐1 β and IL‐6, in the liver. At the same time, various inflammatory factors can act on JAK2/STAT3 signaling pathway and further promote the inflammatory response . Therefore, inhibiting the JAK2‐STAT3 signaling pathway is essential to alleviate the inflammatory response and liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…JAK2 is a major member of the JAK protein family, which can be activated by many cytokines in vivo and phosphorylated with STAT3, an important member of the transcription activator family (STATs) that exists in the nucleus in the form of homologous dimer, to form a JAK2–STAT3 complex; this complex regulates the expression of inflammatory factors, such as TNF‐ α , IL‐1 β and IL‐6, in the liver. At the same time, various inflammatory factors can act on JAK2/STAT3 signaling pathway and further promote the inflammatory response . Therefore, inhibiting the JAK2‐STAT3 signaling pathway is essential to alleviate the inflammatory response and liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ADSCs‐CM treatment is as effective as ADSCs in treating pulmonary hypertension and pulmonary fibrosis and these beneficial effects of CM may provide an advanced approach to treat cardiopulmonary disorders [Rathinasabapathy et al, ]. It has also been established that hypoxic‐conditioned media of adipose‐derived stem cells increases the viability of hepatotoxic hepatocytes and augments liver regeneration in partially hepatectomized mice [Lee et al, ]. Although ADSCs‐CM has various application in wound healing, skin injury, brain injury, liver injury, and many more [Pawitan, ], the role of ADSCs‐CM in insulin resistance has not been established so far.…”
mentioning
confidence: 99%
“…Moreover, Stepniak et al reported that c-Jun/ AP-1 promoted G 1 /S transition in mice hepatocytes through a p53-dependent pathway after PH [28]. In addition, Wnt/ b-catenin, JAK-STAT and MAPK signalling pathways have been proved to be a major regulator of regeneration [29][30][31]. Overview, we hypothesized that DE circRNAs might regulate the expression of downstream mRNAs through their target miRNAs, thereby controlling cell proliferation through above signalling pathways in the proliferation phase of rats LR.…”
Section: Discussionmentioning
confidence: 99%